Association between Lymphocyte Monocyte Ratio and Clinical Staging of Nasopharyngeal Carcinoma (TALENTA PUBLISHER, 2021)
Introduction: Nasopharyngeal cancer (NPC) is the most common head and neck malignancy with an ever-increasing incidence. Inflammatory biomarkers has been proven to be an indicator of immune response against malignancies. A more advanced clinical stage will elicit a worse immune response against tumor cells. A simple and low cost laboratory examination using biomarkers such as lymphocyte monocyte ratio is needed in order to determine the prognosis of NPC patients based on immune response against malignancies. Objective: To determine the association between lymphocyte monocyte ratio and the clinical stage of patients with NPC. Methods: A case control study was used on data obtained from medical records of NPC patients who had undergone staging in the Otolaryngology Outpatient Department of Sardjito Public Hospital from 2015 to 2018. Results: Total of 64 patients were enrolled in the study, comprising of 38 males (59.4%) and 26 females (40.6%). There were 33 (51.6%) patients aged ≤ 50 years and 31 patients (48.4%) aged > 50 years, with early and advanced clinical stages of 32 patients in each age group. The most common histopathological type is undifferentiated carcinoma (WHO Type 3) (60 patients, 93.7%) followed by non-keratinizing carcinoma (WHO Type 2) (4 patients, 6.3%). The cutoff ratio for lymphocyte monocyte ratio was obtained from ROC Curve analysis, which was 2,64. Statistical analysis using chi-square test showed an association between LMR and clinical staging of NPC patients with a p value < 0,001, with an Odds Ratio of 6.53 (CI 95%; 2.19 – 19.42). Thus, patients with a lower LMR was shown to have 6.53 times the risk of having a more advanced clinical stage compared to higher LMR. Conclusion: There was found to be an association between lymphocyte monocyte ratio and clinical staging of nasopharyngeal cancer patients